Internalizing Gratitude to Allah and Environmental Stewardship through Plastic Waste Recycling: An Islamic Ecotheological Study among Students of SD Negeri 5 Kota Bengkulu - Rannesha Ayu Devta Amanda; Muhammad Tommy Indrico; Wildan Nur Hidayat (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
The increasing accumulation of plastic waste has become an environmental challenge that requires educational efforts to build ecological awareness and moral responsibility. This study aims to examine the internalization of gratitude to Allah and environmental stewardship through plastic waste recycling activities among students of SD Negeri 5 Kota Bengkulu from the perspective of Islamic ecotheology. This study employed a qualitative case study approach, with data collected through interviews, observations, and documentation involving principals, teachers, and students. The findings indicate that plastic waste recycling activities serve as an effective medium for integrating environmental education with Islamic values. Students developed an understanding that environmental preservation represents gratitude to Allah and responsibility for safeguarding natural resources entrusted to humanity. These activities also promoted discipline, cooperation, creativity, and ecological awareness. Overall, the study concludes that plastic waste recycling can strengthen both environmental consciousness and Islamic character formation through value-based educational practices.